Fitobiotik Berbasis Tanaman Pekarangan: Inovasi Tepat Guna Bagi Peternakan Ramah Lingkungan di Pulau-Pulau Kecil - Tagueha, Astri Dwyanti; Papilaya, B J; Horhoruw, W M; Souhoka, D F; Siwa, I P; da Costa, J (Universitas Perjuangan Tasikmalaya, 2026)
The livestock sector on small islands in Maluku Province has the potential to optimize local agrosystems through sustainable approach that respects socio-cultural contexts. In this region, livestock farming is predominantly managed by smallholder farmers who depend on natural feed and external resources for medication and marketing purposes. Despite geographical challenges and limited accessibility, farmers can be empowered to independently utilize local resources for sustainable farming. This community service program, implemented across several islands in Maluku, aimed to enhance farmers’ self-reliance by developing backyard-based phytobiotics as a practical innovation to support eco-friendly livestock farming. Phytobiotics were formulated from readily available backyard herbs, including turmeric, ginger, papaya leaves, and betel leaves, which functioned as immunostimulants, natural antimicrobials, and feed efficiency enhancers. The program included training, demonstrations, and continuous mentoring for small ruminant and poultry farmers in several coastal villages on three islands: Ambon, Seram, and Moa. The results showed increased farmer skills in preparing phytobiotics and growing awareness of sustainable livestock farming practices. This initiative demonstrates that utilizing backyard resources for phytobiotics is an ecologically relevant solution for advancing livestock farming in resource-limited island communities.